STUDI NORMATIF ATAS KETENTUAN PENCATATAN NIKAH DAN IMPLIKASINYA TERHADAP LEGALITAS KELUARGA SIRI - Satriya Pamungkas; Ana Billah (USRAH: Jurnal Hukum Keluarga Islam, 2024)
This study aims to normatively analyze the legal provisions on marriage registration in Indonesia and its implications for the legal status of families involved in unregistered (siri) marriages. The research employs a normative legal method using statutory, conceptual, and case approaches. Data sources include primary, secondary, and tertiary legal materials, analyzed descriptively and prescriptively. The findings indicate that marriage registration is a formal legal requirement necessary for a marriage to have legal standing under state law. The absence of registration, as in siri marriages, leads to various legal consequences, including the unrecognized status of wives and children, the loss of inheritance and marital property rights, and the lack of legal protection for women and children. Based on the theories of legal certainty and legal protection, the state holds the responsibility to affirm marriage registration as an essential instrument of legality and the protection of civil rights within the family.